Unstable images : colonial discourse on New Ireland, Papua New Guinea, 1875-1935 - Clay, Brenda Johnson (University of Hawaii Press, 2005)
The subject of colonialism encompasses a multitude of analytic concerns about the nature and extent of political controls, economic inequalities, and social hierarchies. Underlying the varied conditions of power and subordination are the diverse, sometimes contested representations of human difference that motivate, support, or question colonial practices and projects. Unstable Images concentrates a critical gaze on this discursive side of colonialism through close readings of a series of Western texts on the people of New Ireland from the 1870s to the 1930s--when the status of the New Ireland-New Britain region changed from precolonial to German control and finally to a League of Nations mandated Australian administration.